Allosteric Modulation of Class C GPCRs: A Novel Approach for the Treatment of CNS Disorders - Engers, Darren W. (2012)
Allosteric modulation has emerged as an innovative pharmacological approach to selectively activate or inhibit a number of Class C GPCRs. Of the Class C GPCRs, metabotropic glutamate (mGlu) receptors represent the most promising candidates for clinical success, and both positive allosteric modulators (PAMs) and negative allosteric modulators (NAMs) of mGluRs have demonstrated therapeutic potential for a range of psychiatric and neurological disorders such as pain, depression, anxiety, cognition, Fragile X syndrome, Parkinson’s disease and schizophrenia.